Irish periodicals in their Atlantic context, 1770-1830 : the monthly and quarterly magazines of Dublin, with comparison to those of Edinburgh and Philadelphia - Archbold, Johanna (Trinity College (Dublin, Ireland). Department of History, 2008)
This thesis focuses on the development of Irish periodical literature from 1770-1830. Irish periodicals have received relatively little attention in the historical literature of the period, beyond quantitative lists, and a handful of detailed studies of particular titles. Their basic history has been outlined in general surveys of the literature, though these have tended to be focused in either the eighteenth or the nineteenth centuries. The intention here is to examine the ninety monthly, bi-monthly and quarterly periodicals of a sixty year period which bridges both centuries.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin